Phenanthro[9, 10-d]triazole and imidazole derivatives: high triplet energy host materials for blue phosphorescent organic light emitting devices. Issue 6 (11th March 2019) - Idris, Muazzam; Coburn, Caleb; Fleetham, Tyler; Milam-Guerrero, JoAnna; Djurovich, Peter I.; Forrest, Stephen R.; Thompson, Mark E.
Abstract : A class of wide bandgap host materials is introduced as an alternative to carbazole-based hosts to enhance the efficiency and transport properties of organic light emitting diodes (OLEDs). Abstract : A class of wide bandgap host materials is introduced as an alternative to carbazole-based hosts to enhance the efficiency and transport properties of organic light emitting diodes (OLEDs). We have synthesized and investigate the photophysical and electrochemical properties of a series of phenanthrene derivatives incorporating fused triazole or imidazole rings. The resulting phenanthro[9, 10- d ]triazoles and phenanthro[9, 10- d ]imidazoles are suitable host materials for blue phosphors due to their high triplet energies and conductivities. Incorporation of bulky substituent groups leads to retention of the high triplet energies in the solid state. The most promising materials are incorporated in blue phosphorescent OLEDs that achieve external quantum efficiencies >20%.